Additive impact of metabolic syndrome and sarcopenia on all-cause and cause-specific mortality: an analysis of NHANES - Zhang, Meng; Zeng, Qing-Yue; Zhuang, Linli (Frontiers in Endocrinology, 2025)
BackgroundMetabolic syndrome (MetS) and sarcopenia (SP) are increasingly significant public health issues in aging societies, sharing common pathophysiological mechanisms and being associated with severe health consequences. This study investigates the impact of MetS and SP on all-cause and cause-specific mortality using a longitudinal, nationally representative population-based cohort.MethodsThe study analyzed data from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2018. Mortality data were obtained from the National Death Index up to December 2019.ResultsAmong the 21,962 participants, 13,517 (61.5%) had neither MetS nor SP(MetS-/SP-), 5,407 (24.6%) had MetS only(MetS+/SP-), 2,698 (12.2%) had SP only(MetS-/SP+), and 340 (1.5%) had both MetS and SP(MetS+/SP+). Compared to the group without MetS and SP, the groups with MetS only, SP only, and both MetS and SP showed increased all-cause mortality, with adjusted hazard ratios (HR) of 1.23 (95% CI: 1.11-1.37), 1.63 (95% CI: 1.41-1.89), and 1.61 (95% CI: 1.33-1.95), respectively. The MetS+/SP+ group had the highest overall mortality risk (trend test p<0.0001). For cause-specific mortality, the MetS+/SP+ group exhibited increased cardiovascular mortality (HR: 1.89, 95% CI: 1.27-2.81), cardiac mortality (HR: 1.89, 95% CI: 1.25-2.86), respiratory mortality (HR: 2.63, 95% CI: 1.29-5.35), and diabetes mortality (HR: 8.79, 95% CI: 2.62-29.45) compared to the group without MetS and SP.ConclusionThe coexistence of MetS and SP significantly increases the risk of all-cause and cause-specific mortality. Individuals with either condition may require more vigilant management to prevent the onset of the other condition, thereby reducing mortality rates. These findings highlight the importance of integrated healthcare strategies targeting both MetS and SP to improve patient outcomes and longevity.